Religion and right-wing populism in Italy: using 'Judeo-Christian roots' to kill the European Union. Issue 1 (1st January 2019) - Molle, Andrea
ABSTRACT: This contribution offers new directions to explore how implicitly religious customs and norms may influence voting for right-wing populist parties. It also suggests an indirect influence of government regulation of religion on the rise of populism in the European Union. The church–state relationship is viewed as providing a stable context for religious biases to emerge, thereby enabling populist forces to capitalise on a sense of loss of national identity which in turn reinforces citizens' negative attitude towards immigrants, particularly of different religious backgrounds. Combining the Religion and State Project Round 3 (RAS3) dataset with electoral and socio-demographic data, this contribution presents time-series analyses and linear regression in order to explore the impact of religious factors on populist voting patterns and support for the Italian Eurosceptic populist movement, the League, between 1992 and 2014. I argue that the success of this populist party lies in its ability to use an adaptive mythology that plays on pre-existing religious norms to stoke fears of a decline of cultural homogeneity and a loss of political and economic power.